Узловые разработки ученых и выпускников НТУ "ХПИ" в области информационно коммуникационных технологий - Назаренко, Сергей Александрович (My University, 2016)
Сделан обзор основных научно-технических достижений ученых и выпускников НТУ "ХПИ" в области информационно коммуникационных технологий в 19-21 столетии. Краткая информация приведена об основных этапах развития информационно коммуникационных технологий, а также о деятельности А. М. Ляпунова, В. А. Стеклова, Н. Д. Пильчикова, А. Н. Щукарева, Джерри Неймана, Н. А. Явлинского, С. М. Осовца, Я. Е. Айзенберга, А. И. Кривоносова, А. П. Биленко, В. А. Ковалевского, В. В. Петрова, Юджина Мамута и других.

The paper is concerned with the dynamic process of establishment and development of the research and pedagogic activity of the scientists and graduates of the National Technical University "Kharkiv Polytechnic Institute" (NTU "KhPI") in the field of information technology in the 19-21 centuries. The fundamental scientific trends of evolution of information technology were discovered and explored here. The world-famous scientists who worked at the NTU "KhPI" or graduated it are mentioned.
Distinguished achievements of the scientists and graduates of of the NTU "KhPI" in the field of information technologies
Keywords: информационно коммуникационные технологии; электронно-вычислительная техника; Нейман Джерри; компьютерная механика; виртуальное моделирование; НТУ "ХПИ" история; Национальный технический университет "Харьковский политехнический институт"; выпускники НТУ "ХПИ"; information technology; CAE systems; Neyman; SPDM; computer